2020
DOI: 10.1186/s41182-020-00204-z
|View full text |Cite
|
Sign up to set email alerts
|

Praziquantel is an effective drug for the treatment of Schistosoma Mansoni infection among school-aged children in Northwest Ethiopia

Abstract: Background: The appropriate drug for the treatment of schistosomiasis is praziquantel. However, low cure rate and existence of drug resistance both in vivo and in vitro were reported in different endemic areas. Hence, the aim of this study was to evaluate the effectiveness of praziquantel for Schistosoma mansoni (S. mansoni) treatment. Methods: A cross-sectional study was conducted in Sanja General Primary School, North Gondar Zone, Amhara region, Northwest of Ethiopia, from March to April, 2017. A total of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…This result is higher when compared to studies carried out in Western Kenya 16.3% (10), Kwale, 0.0% 11 In the current study S. mansoni intensity of study participants was 30.5%, 27.0% and 42.6% for light, moderate, and heavy infection, respectively. The present study has high proportion of heavy intensity of infection, compared with a report from Western Kenya, (9.8%)(10), Sanja, Northwest Ethiopia, (18.7%) (32), Sanja, Northwest Ethiopia, (36.3%) (26), and Addiremets town, Western Tigray, Ethiopia, (16.7%) (21). Similarly, In Mbita District, Western Kenya, the intensity of infection was 16.1% heavy infections (25).…”
Section: Discussioncontrasting
confidence: 48%
“…This result is higher when compared to studies carried out in Western Kenya 16.3% (10), Kwale, 0.0% 11 In the current study S. mansoni intensity of study participants was 30.5%, 27.0% and 42.6% for light, moderate, and heavy infection, respectively. The present study has high proportion of heavy intensity of infection, compared with a report from Western Kenya, (9.8%)(10), Sanja, Northwest Ethiopia, (18.7%) (32), Sanja, Northwest Ethiopia, (36.3%) (26), and Addiremets town, Western Tigray, Ethiopia, (16.7%) (21). Similarly, In Mbita District, Western Kenya, the intensity of infection was 16.1% heavy infections (25).…”
Section: Discussioncontrasting
confidence: 48%
“…This might be associated with the high endemicity of the disease in the Amhara region. Several studies indicated high prevalence (>83%) of S. mansoni in the region [ 12 , 13 , 38 ]. The high prevalence and intensity of infection may contribute to the slightly lower efficacy of praziquantel in the region.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a higher cure rate of praziquantel was reported among individuals infected with S. mansoni than those infected with S. haematobium in Cameroon [51]. e difference in the the region [12,13,38]. e high prevalence and intensity of infection may contribute to the slightly lower efficacy of praziquantel in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review was conducted in order to estimate the pooled cure rate and egg reduction rate of PZQ against Schistosoma mansoni infection among pre-school and school age children from 2002 [28] up to 2020 [33]. In this systematic review and meta-analysis, the cure rate of PZQ against Schistosoma mansoni infection among children ranges from 73.6% to 99.1% with an overall pooled CR of 86.65% with 95% CI of 83.4%-93.9%.…”
Section: Discussionmentioning
confidence: 99%